Microbial Methanogenesis and Acetate Metabolism in a Meromictic Lake - Winfrey, M. R. (1979)
Methanogenesis and the anaerobic metabolism of acetate were examined in the sediment and water column of Knaack Lake, a small biogenic meromictic lake located in central Wisconsin. The lake was sharply stratified during the summer and was anaerobic below a depth of 3 m. Large concentrations (4,000 μmol/liter) of dissolved methane were detected in the bottom waters. A methane concentration maximum occurred at 4 m above the sediment. The production of (14)CH(4) from (14)C-labeled HCOOH, HCO(3)(−), and CH(3)OH and [2-(14)C]acetate demonstrated microbial methanogenesis in the water column of the lake. The maximum rate of methanogenesis calculated from reduction of H(14)CO(3)(−) by endogenous electron donors in the surface sediment (depth, 22 m) was 7.6 nmol/h per 10 ml and in the water column (depth, 21 m) was 0.6 nmol/h per 10 ml. The methyl group of acetate was simultaneously metabolized to CH(4) and CO(2) in the anaerobic portions of the lake. Acetate oxidation was greatest in surface waters and decreased with water depth. Acetate was metabolized primarily to methane in the sediments and water immediately above the sediment. Sulfide inhibition studies and temperature activity profiles demonstrated that acetate metabolism was performed by several microbial populations. Sulfide additions (less than 5 μg/ml) to water from 21.5 m stimulated methanogenesis from acetate, but inhibited CO(2) production. Sulfate addition (1 mM) had no significant effect on acetate metabolism in water from 21.5 m, whereas nitrate additions (10 to 14,000 μg/liter) completely inhibited methanogenesis and stimulated CO(2) formation.